A 3D Measurement and Computerized Meshing Study to Promote Bus Ridership Among People Using Powered Mobility Aids - Unsworth, Carolyn A.; Chua, Julian; Gudimetla, Prasad (Frontiers in Built Environment, 2020)
People who use powered mobility aids such as wheelchairs and scooters need and want to use public transport. Buses are the most affordable and efficient form of public transport, capable of connecting people across local communities. However, with curbside rather than platform boarding and internal space limitations, buses also present many accessibility challenges for people using mobility aids during ingress, egress, and interior maneuverability. In Australia, people using mobility aids board low floor buses that are required to comply with the national bus accessibility standard, using the front doors. A new standard was recently created to provide a Blue Label identification for powered mobility aids suitable to access public transport. The accuracy of this standard to identify mobility aids suitable to use on buses has not been verified. This research used a world-first methodology that included 3-Dimensional (3D) scanning of 35 mobility aids and 21 buses. The resulting 735 scan combinations were efficiently meshed using Meshlab, an open-source software. The research demonstrated that (i) although none of the buses were compliant with the relevant standard in 3D, many could still facilitate the boarding of a variety of mobility aids, and (ii) the Blue Label, while a valuable guide, did not accurately identifying all mobility aids that would and would not be able to board buses. This research has shortlisted nine mobility aids that can be recommended to consumers as being able to fit all the full-size buses tested. The dimensions of mobility aids that appear to enable access on most buses were also identified for consumers to consider when purchasing a mobility aid. The novel 3D meshing methodology used in this research also revealed that most collision points between mobility aids and buses occur in the curved-corridor entry of the buses. To minimize this entry problem, future bus boarding designs should consider the option of double-door entry/exit in the middle of the bus, which is common in many other countries. Adoption of this strategy would mitigate some of the challenges that people using mobility aids encounter when accessing buses, thereby increasing public transport ridership among this group.